Eighteenth workshop on geothermal reservoir engineering: Proceedings - Ramey, H.J., Jr.; Horne, R.J.; Kruger, P.; Miller, F. G.; Brigham, W. E.; Cook, J. W. (Stanford University, 1993)
PREFACE The Eighteenth Workshop on Geothermal Reservoir Engineering was held at Stanford University on January 26-28, 1993. There were one hundred and seventeen registered participants which was greater than the attendance last year. Participants were from eight foreign countries: Italy, Japan, United Kingdom, Mexico, New Zealand, the Philippines, Guatemala, and Iceland. Performance of many geothermal fields outside the United States was described in several of the papers. Dean Gary Ernst opened the meeting and welcomed the visitors to the campus. The key note speaker was J.E. ''Ted'' Mock who gave a brief overview of the Department of Energy's current plan. The Stanford Geothermal Program Reservoir Engineering Award for Excellence in Development of Geothermal Energy was awarded to Dr. Mock who also spoke at the banquet. Thirty-nine papers were presented at the Workshop with two papers submitted for publication only. Technical papers were organized in twelve sessions concerning: field operations, The Geysers, geoscience, hot-dry-rock, injection, modeling, slim hole wells, geochemistry, well test and wellbore. Session chairmen were major contributors to the program and we thank: John Counsil, Kathleen Enedy, Harry Olson, Eduardo Iglesias, Marcelo Lippmann, Paul Atkinson, Jim Lovekin, Marshall Reed, Antonio Correa, and David Faulder. The Workshop was organized by the Stanford Geothermal Program faculty, staff, and graduate students. We wish to thank Pat Ota, Ted Sumida, and Terri A. Ramey who also produces the Proceedings Volumes for publication. We owe a great deal of thanks to our students who operate audiovisual equipment and to John Hornbrook who coordinated the meeting arrangements for the Workshop. Henry J. Ramey, Jr. Roland N. Horne Frank G. Miller Paul Kruger William E. Brigham Jean W. Cook